(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
The aim of this paper is to give an overview of literary works of Virginia Woolf, mostly of her novels and point to the influences and changes that inspired her modernist and feminist thought, resulting in recognition of her as a major female modernist writer of her age. The second part of the paper deals with the issue of androgyny, which is crucial in Woolf’s artistic creation and is present in both her novels and her essays. Different critical approaches speak in favour of an androgynous spirit of this modernist writer, emphasizing complexity of her art.